Synthesis, characterization and applications of gold nanoparticles - BHARATHI.P (International Journal of Pharma and Bio Sciences, 2019)
This mini review is devoted mainly to the description of synthesis, characterization and applications of gold nanoparticles (GNPs) in the field of science and technology. The size decreases from bulk solid to nano, the properties of GNPs changed and it behaves completely different from their original size. GNPs are being used for an all times growing in number of applications. The composition, dimension and morphology of engineered GNPs enable their use in variety of areas such as electronic, biomedical, pharmaceutical, cosmetic, energy, environmental, catalysis and materials science. Nowadays many growing fields are in need of various advance techniques to meet demands, overcome the issues and making good in all. GNP in particular and their application in diagnostics have received a lot of attention from the scientific community. GNP have major advantages compared to bulk solvent. The nanoparticles provide a large surface area that promotes efficient macromolecular interactions, effective signal amplification. Its have unique optical properties are surface plasmon resonance absorption and resonance light scattering. Previously, Sayedet al. (2007) reported the surface-plasmon resonance-enhanced optical properties of colloidal GNPs directed towards biomedical applications with an emphasis on cancer diagnostics and therapeutics. The features of surface plasmon resonance, light-scattering and surface-enhanced emission of GNP is used in easy detection of cancer. The purpose of this review is to provide an overview of preparation methods of ecofriendly GNPs and describe the physico-chemical characterization of GNPs. Additionally the main issues and concerns regarding to societal implications of rapid development GNPs in various fields of science and technology are being discussed.